A geometric morphometrics comparative analysis of Neandertal humeri (epiphyses-fused) from the El Sidrón cave site (Asturias, Spain). Issue 82 (May 2015) - Rosas, Antonio; Pérez-Criado, Laura; Bastir, Markus; Estalrrich, Almudena; Huguet, Rosa; García-Tabernero, Antonio; Pastor, Juan Francisco; Rasilla, Marco de la
Abstract: A new collection of 49, 000 year old Neandertal fossil humeri from the El Sidrón cave site (Asturias, Spain) is presented. A total of 49 humeral remains were recovered, representing 10 left and 8 right humeri from adults, adolescents, and a juvenile (not included in the analyses). 3D geometric morphometric (GM) methods as well as classic anthropological variables were employed to conduct a broad comparative analysis by means of mean centroid size and shape comparisons, principal components analysis, and cluster studies. Due to the fragmentary nature of the fossils, comparisons were organized in independent analyses according to different humeral portions: distal epiphysis, diaphysis, proximal epiphysis, and the complete humerus. From a multivariate viewpoint, 3D-GM analyses revealed major differences among taxonomic groups, supporting the value of the humerus in systematic classification. Notably, the Australopithecus anamensis (KP-271) and Homo ergaster Nariokotome (KNM-WT 15000) distal humerus consistently clusters close to those of modern humans, which may imply a primitive condition for Homo sapiens morphology. Australopithecus specimens show a high degree of dispersion in the morphospace. The El Sidrón sample perfectly fits into the classic Neandertal pattern, previously described as having a relatively wide olecranon fossa, as well as thin lateral and medial distodorsal pillars. These characteristics were also typical of the Sima de los Huesos (Atapuerca) sample, African mid-Pleistocene Bodo specimen, and Lower Pleistocene TD6-Atapuerca remains and may be considered as a derived state. Finally, we hypothesize that most of the features thought to be different between Neandertals and modern humans might be associated with structural differences in the pectoral girdle and shoulder joint.